PEMANFAATAN ECENG GONDOK (EICHHORNIA CRASSIPES (MART.) SOLMS.) DALAM PENYISIHAN LOGAM BERAT CHROM (CR) PADA LIMBAH ELEKTROPLATING - Sri Sumiyati; Mochtar Hadiwidodo (TEKNIK, 2007)
Effluent that is produce by the electroplating industry, especially nickel chrome plating, contains chromemetal that is carcinogenic. The toxicities from chrome are caused by its ability to dissolve and it’s mobilityin the environment. An alternative treatment to reduce chrome is called fitoremediasi which uses plants asits indicator; in this case we use water hyacinth.At the preface experiment, we tried to plant mature water hyacinth in electroplating waste. First we tried toplant in 100% waste water in witch we repeated it 3 times. At the 3rd week; day 18; the plants becameyellowish and became wilted. Knowing this fact, we applied the time for our experiment the we were goingto executed, with assuming at the 18th day the plants will become wilted as an indicator that the waterhyacinth are saturated in adsorbing chrome as the heavy metal pollutant. This became the parameter indesigning the time treatment for the plant zone, 4 until 15 days.The treatment was done by making variation in the amount of plants that are planted, which was 0 plants(as the control), 1 plant, 2 plants, 3 plants, and 4 plants; with 3 times repeating at each stage. The result ofthis experiment after 18 days shows the chrome concentration and the efficiently in decreasing theconcentration on each stage. The highest efficiently for each plant was the treatment by 1 plant only. Thehighest efficiently in decreasing the concentration was 78,95% ad it was done by the treatment with 4plants. To get chrom concentration which is fill with the standard, we can add more water hyacinth into thewaste with the balance equivalent or we need the lower beginning concentration.